Hydrothermal Synthesis of Graphene Quantum Dots Supported on Three-Dimensional Graphene for Supercapacitors - Luo, Peihui (Nanomaterials (Basel), 2019)
Incorporation of new functional components into a three-dimensional graphene (3DG) framework improves the performance of supercapacitors based on 3DG as electrodes by tailoring the framework’s structure and properties. In this work, graphene quantum dots (GQDs) were incorporated into 3DG via one-step hydrothermal treatment of GQDs and graphene oxide (GO). By simply adjusting the GQDs/GO feeding ratio by weight, various GQDs/3DG composites were formed. The maximum feeding ratio was 80%, and the prepared composites possessed saturated GQDs loading on the 3DG framework, whereas composites obtained with a GQDs/GO feeding ratio of 40% as electrodes exhibited optimal specific capacitance of 242 F·g(−1) for supercapacitors, an increase of 22% compared with that of pure 3DG electrodes (198 F·g(−1)). This improved performance was mainly due to better electrical conductivity and larger surface area for GQDs/3DG composites with moderate GQDs content. The fabricated GQDs/3DG composites as electrodes for supercapacitors revealed high electrochemical stability. Their capacitance kept 93% of the initial value after 10,000 charge-discharge cycles.